Bonding strength and thermal shock resistance of a novel bilayer (c‐AlPO4‐SiCw‐mullite)/SiC coated carbon fiber reinforced CMCs. Issue 1 (1st August 2019) - Chen, Pengju; Xiao, Peng; Li, Zhuan; Pan, Ling; Li, Jinwei; Liu, Zeyan; Pu, Dongmei; Li, Yang
Abstract: Mullite coating, SiC whiskers toughened mullite coating (SiCw ‐mullite), and cristobalite aluminum phosphate ( c ‐AlPO4 ) particle modified SiCw ‐mullite coating ( c ‐AlPO4 ‐SiCw ‐mullite) were prepared on SiC coated C/SiC composites using a novel sol‐gel method combined with air spraying. Results show that molten SiO2 formed by the oxidation of SiC whiskers and molten c ‐AlPO4 improved the bonding strength between mullite outer coating and SiC–C/SiC composites due to their high‐temperature bonding properties. The bonding strength between mullite, SiCw ‐mullite, c ‐AlPO4 ‐SiCw ‐mullite outer coatings and SiC–C/SiC composites were 2.41, 4.31, and 7.38 MPa, respectively. After 48 thermal cycles between 1773 K and room temperature, the weight loss of mullite/SiC coating coated C/SiC composites was up to 11.61%, while the weight losses of SiCw ‐mullite/SiC and c ‐AlPO4 ‐SiCw ‐mullite/SiC coatings coated C/SiC composites were reduced to 7.40% and 5.12%, respectively. The addition of appropriate SiC whiskers can considerably improve the thermal shock resistance of mullite coating owing to their excellent mechanical properties at high temperature. In addition, c ‐AlPO4 particles can further improve the thermal shock resistance of SiCw ‐mullite coating due to their high‐temperature bonding and sealing properties. No obvious micro‐pores and cracks were observed on the surface of c ‐AlPO4 ‐SiCw ‐mullite coating after 48 thermal cycles due to timely healing effect by formation of secondary mullite.